Assessing Consumer Confidence in Halal Authorities: A Comparative Study between Malaysia and Brunei - Ramlan, Nadiah; Sahari, Noorul Huda; Shafie, Nur Amalina; Usop, Nur Izyan Syazwanie; Said, Shahirah; Izham, Siti Sarah (Indonesian Journal of Halal Research, 2025)
The rapid growth of the halal market, driven by increasing Muslim consumer demand, has led to the establishment of halal certification bodies such as Malaysia's Department of Islamic Development (JAKIM) and Brunei's Halal Food Control Division (HFCD) under the Ministry of Religious Affairs (MoRA) to ensure compliance with Islamic dietary laws. However, recent halal integrity issues, including product contamination and certification fraud, have raised concerns about the effectiveness and trustworthiness of these authorities. This study aims to examine Muslim consumer trust in JAKIM and HFCD, exploring the factors influencing their confidence in halal certification processes. This study used a quantitative approach to collect primary data from 300 Muslim individuals in both countries using online surveys. The analysis is conducted using descriptive and factor analysis methods using SPSS V.2. The study revealed that despite high awareness of recent halal issues, Muslim consumers in Malaysia and Brunei maintain significant trust in their respective halal authorities, JAKIM and HFCD. Multiple linear regression analysis confirmed that halal knowledge (β= 0.362), attitude (β= 0.292), and awareness coupled with willingness (β= 0.158) were significant factors influencing consumer trust, while environmental factors were not statistically significant. The high educational background of respondents contributed to a strong understanding of halal integrity, reinforcing confidence in the authorities. Furthermore, media influence and prior exposure to halal food fraud shaped consumer perceptions, leading to increased inspection of halal certification. These findings highlight the critical role of transparency, constricted regulatory enforcement, and continuous engagement in sustaining consumer confidence in halal certification bodies.